Relationship Between Quorum Sensing and Secretion Systems - Pena, Rocio Trastoy; Blasco, Lucia; Ambroa, Antón; González-Pedrajo, Bertha; Fernández-García, Laura; López, Maria; Bleriot, Ines; Bou, German; García-Contreras, Rodolfo; Wood, Thomas Keith; Tomás, Maria (Frontiers in Microbiology, 2019)
Quorum sensing (QS) is a communication mechanism between bacteria that allows specific processes to be controlled, such as biofilm formation, virulence factor expression, production of secondary metabolites and stress adaptation mechanisms such as bacterial competition systems including secretion systems (SS). These SS have an important role in bacterial communication. SS are ubiquitous; they are present in both Gram-negative and Gram-positive bacteria and in Mycobacterium sp. To date, 8 types of SS have been described (T1SS, T2SS, T3SS, T4SS, T5SS, T6SS, T7SS and T9SS). They have global functions such as transport of proteases, lipases, adhesins, heme-binding proteins, amidases; and specific functions such as the synthesis of proteins in host cells, adaptation to the environment, the secretion of effectors to establish an infectious niche, transfer, absorption and release of DNA, translocation of effector proteins or DNA and autotransporter secretion. All of these functions can contribute to virulence and pathogenesis. In this review, we describe all types of secretion systems and discuss the ones that have been shown to be regulated by QS. Due to the large amount of information about this topic in some pathogens, we focus mainly on Pseudomonas aeruginosa and Vibrio sp.